Imaging and management of fibroepithelial breast lesions on percutaneous core needle biopsy. Issue 6 (10th January 2020) - Cheema, Hena S.; Mehta, Rashmi; Slanetz, Priscilla J.
Abstract: The purpose of this study is to review the clinical presentation, multi‐modality appearance, and management of the most common benign and malignant fibroepithelial lesions of the breast. Fibroepithelial lesions of the breast may exhibit characteristic features on mammography, ultrasound, and MRI, although definitive diagnosis most often requires biopsy and at times, surgical excision. Knowledge of the imaging features can assist in refining the differential diagnosis and guiding appropriate management.